Spirit-of-This-World Encounters Spirit-of-Tragedy. Issue 1 (1st May 2014) - Jinli, He; Jones, David
Abstract China's encounter with Western cultures since the late Qing was generally viewed as a one-side "borrowing" and a radical "break" from traditional culture. "Westernization" became the dominant characteristic of the descriptions and interpretations of modern Chinese culture. Although Wang's work on comparative Chinese and Western philosophical studies has received much attention, there has been little attention given to the problem of Western influences, the domination of which, when appraising Wang's thought has persisted for a long time and has caused many misunderstandings regarding his literary-aesthetic and philosophical thinking. Using the hermeneutical lens of Kierkegaard and especially Heidegger to look through to help correct our vision of interpreting Wang in light of his own culture, we propose that there is a specific Chinese sensibility crucial for understanding his use of Schopenhauer and Nietzsche, a sensibility that has been ignored by those who later sought to reconstruct and evaluate his earlier studies. We use the idea of "tragedy" heuristically to show the connections and differences between Wang Guowei and Schopenhauer and propose how renjian jingshen (spirit-of-this [human] world) played an important role in Wang's cultural "borrowing" from Schopenhauer. Such a conclusion is contrary to the common understanding of Wang as a devoted follower of Schopenhauer's "pessimistic" philosophy.